Taxonomy and molecular phylogeny of the Amiota nagatai species group (Diptera: Drosophilidae) - He, Xiaofang; Jiang, Jian-Jun; Cao, Hua-Zhi; Chen, Hong-Wei (Zootaxa, 2009)
Three new species of the Amiota nagatai species group were described from southern China: A. bachlii Cao and Chen, sp. nov., A. chengyuae Cao and Chen, sp. nov. and A. protuberantis Cao and Chen, sp. nov. A key to all the species of this group was provided. The phylogenetic relationship in this group was investigated based on DNA sequences of the mitochondrial NADH dehydrogenase subunit 2 (ND2) gene, with two species of the genus Amiota taken as outgroups.